(untitled) (New York, 2009)
"Given the critical importance of information systems and technology for businesses today, this new and updated edition covers the breadth of topics relevant for managing information strategically. By bringing together contributions addressing contemporary issues and challenges that every manager is likely to face, Professors Galliers and Leidner have produced a most valuable and accessible volume. A must read for anyone with managerial ambitions." Joe Peppard, Cranfield School of Management, UK
Keywords: Information technology,Management information systems,Strategic planning; Management